Combining Ability of Indonesian Tropical Maize in Two Different Seasons - Suyadi, Suyadi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Testing an inbred cross for hybrid development requires a proper test cross method. The diallel is one crossing method to find out the magnitude of inbred combining ability, both general general (GCA) and specific combining ability (SCA) and specific combining ability, that is useful in hybrid development. The objective of the study is to determine the GCA, SCA and heterosis of 6 inbred lines in two seasons. All the inbreds were crossed in diallel design and further evaluated for their combining ability and genetic ratio following the respective methods of Griffing and Baker. The results revealed that GCA, SCA and Reciprocal (REC.) were influenced by planting seasons for almost all yield and yield-related traits. Non-additive gene action was more important in controlling ear length, ear row number, shelled ear weight and yield. The best GCA for yield trait was detected on inbreds G2 and G5. The conclusion from the interpretation of both SCA and REC. is that the inbred crosses of G1 x G6, G2 x G5, G4 x G6, and G5 x G6 have the best yields followed by high heterosis values.